Dynamics Analysis on Piezoelectric Laminated Vibrator and Optimization of PZT Position - Caiqi Hu; Xiaoqi Hu; Jing Ji; Jude Liu; Shengduo Li (Shock and Vibration)
Piezoelectric laminated structure is widely used as actuator’s drive part. The different position of PZT on a piezoelectric vibrator causes different incentive effects. Therefore, seeking an optimal PZT position is of great significance to improve actuator’s drive forces and electromechanical conversion efficiency. In this research, the optimization of PZT position was studied using the approximate solution of piezoelectric vibrator mode shape with mutation sections. The vibration mode function was expressed as a linear superposition of the admissible function according to Rayleigh Ritz method. Then solving of functional variation was converted into the solving of the coefficient matrix of the admissible function by Hamilton’s principle. Through analyzing the forms of admissible functions, the admissible functions that satisfied the boundary conditions of displacement were chosen. For a given vibrator, approximate function for natural frequency and vibration mode was calculated in given admissible functions. Calculated values and experimental results were compared. Results showed that the more items an admissible function sequence had the closer the calculated results were to the experimental values. The errors of calculations were analyzed based on the selection of admissible functions and electromechanical coupling effect. Optimization of PZT position was achieved by analyzing the mode forces of the piezoelectric laminated vibrator.